Raman spectroscopy revealing noble gas adsorption on single-walled carbon nanotube bundles - Cunha, Renato; Paupitz, Ricardo [UNESP]; Yoon, Kichul; Van Duin, Adri C.T.; Elías, Ana Laura; Carozo, Victor; Dasgupta, Archi; Fujisawa, Kazunori; Lopez, Néstor Perea; Araujo, Paulo T.; Terrones, Mauricio (Elsevier, 2018)
The interaction of the noble atoms (Ar and Xe) with single-walled carbon nanotube (SWCNT) bundles are investigated using Raman spectroscopy in conjunction with computational modeling known as ReaxFF force field. SWCNT bundles were deposited on transmission electron microscopy (TEM) grids, and different noble gases were adsorbed onto the nanotubes at 20 K. Raman spectra acquired show significant frequency blueshifts of the radial breathing mode (RBM), G- and G′(or 2D)-bands due to gas solidification within the external groove sites (free spaces between the tubes in the bundle) and external surfaces of the bundles. This solid shell formed by the adsorbed gases contributes with a hydrostatic pressure to the system. We show from Raman measurements that the frequencies found after gas adsorption exhibit almost the same shifts indicating that the interactions between SWCNTs bundles and the gases (Ar or Xe) are nearly identical.
Keywords: Adsorption; Raman spectroscopy; Simulation